Party Princess - Cabot, Meg (New York : HarperTeen, 2008)
When the student government that Mia presides over goes bankrupt, Grandmère has an elaborate plan to both raise money, which will bring Mia fame, and to link her romantically with a teen bachelor who is not her boyfriend.
Originally published: New York : HarperCollins, c2006.
Keywords: Princesses -- Fiction; Student government -- Fiction; Parties -- Fiction; High schools -- Fiction; School stories; Diaries -- Fiction; Fiction